Internationalization Process of Siemens AG_ The case study of Siemens in Vietnam - Le, Thuy Duong (2017)
Siemens (or Siemens AG) is one of the world largest MNCs with its core business in high technology and its representation in more than 200 countries/regions in all over the global and approximately 85% of its revenue comes from outside Germany (Siemens AG, 2016). Siemens transnational activities started very soon in 1850, only two years after its establishment in 1847, by starting its representative in London. Recently, South East Asia is the region with the highest growth rate and Vietnam which considered as a typical of emerging markets play an important role in this growth. Siemens’s first presence in Vietnam was in 1979 when it installed two steam turbines for a paper company. In 1993, Siemens Vietnam was officially established and since then, the company successfully implemented many key infrastructure projects and has steadily increased its market presence in the country (Siemens Vietnam, 2014). Combining this information background of the company and the major internationalization problems rose above, this dissertation examines two main research questions in order to describe the internationalization process and strategy of Siemens in Vietnam: